Pro .NET Best Practices - Ritchie, Stephen (Apress : Imprint: Apress, 2011)
Pro .NET Best Practices is a practical reference to the best practices that you can apply to your .NET projects today. You will learn standards, techniques, and conventions that are sharply focused, realistic and helpful for achieving results, steering clear of unproven, idealistic, and impractical recommendations. Pro .NET Best Practices covers a broad range of practices and principles that development experts agree are the right ways to develop software, which includes continuous integration, automated testing, automated deployment, and code analysis. Whether the solution is from a free and open source or a commercial offering, you will learn how to get a continuous integration server running and executing builds every time code changes. You will write clearer and more maintainable automated testing code that focuses on prevention and helping your .NET project succeed. By learning and following the .NET best practices in this book, you will avoid making the same mistakes once. With this book at your side, you'll get: Real-world, no-nonsense approaches to continuous integration, automated testing, automated deployment, and code analysis Tips and tricks you'll need to clear hurdles that keep others from putting these common sense ideas into common practice Guidance from the minimal, essential approach all the way to what's necessary to deliver at the highest levels of quality and effectiveness Benefit immediately, even before finishing it, from the knowledge, workable advice, and experience found in Pro .NET Best Practices.